Substance Use and Perceived Consequences on Health and Safety among Commercial Motorcyclists in Ibadan North Local Government, Ibadan, Nigeria (2014)
Introduction: Motorcycling is a globalized mode of transport patronized by many road users especially in Nigeria. Although, fraught with negative health outcomes. This study sought to access the perceived consequences of substance use on health and safety among commercial motorcyclists in Ibadan, Nigeria. Design and Method: Using a cross-sectional survey design, registered and consenting eighty commercial motorcyclists were recruited. A 39 item, interviewer-administered questionnaire containing motorcyclists’ demographic characteristics, perceived consequence of substance use, behaviour towards substance use and consequences of substance use was used to obtain information. Collected data was analyzed at p≤0.05 of significance. Results: The respondents were mainly within 30-39 years (36.3%); previously traders (42.5%) and have attained secondary school level of education (45.0%). Though, 57.5% of the respondents positively affirmed the ability of an individual under the influence of alcohol to cause accident, 46.3% of them hold the belief that it is good for mood modification and did not affect health negatively (70%). Up to 36.2% of the respondents agreed to have used substances while driving. Enhancement of visibility while driving (51.3%), relaxation (47.5%) and assists in forgetting problems (42.5%) were reasons given by motorcyclists for this. Fifty percent of the motorcyclists have been involved in a fatal accident. There no significant association between educational level and perception about substance use at p=0.258 but association between perception on substance use and age of respondents was significant at p=0.05. The Perception and Behavior of motorcyclists’ Riders were significantly different at p= 0.04. Conclusion: Although, the respondents know that substance use had some negative consequences, yet many still indulged in it even when on duty. Positive behavioural change interventions should be implemented among motorcyclists.